Effect of Food Quality, Product Innovation and Trust on Customer Satisfaction (Case Study at McDonald's Bengkulu City) - Ewinda Novita Sari; Tezar Arianto (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of food quality, product innovation and trust on customer satisfaction (Case Study at McDonald's Bengkulu City). This type of research is a quantitative approach. The population in this study were all customers at McDonald's Bengkulu. The sample in this study amounted to 96 respondents. Data collection techniques using observation and questionnaires. This research uses validity test, reliability test, classical assumption test, multiple linear regression test followed by hypothesis testing. Based on the results of the study, it shows that (X1) Food quality has a significant effect on customer satisfaction at McDonald's in Bengkulu City, thus the higher the food quality, the higher customer satisfaction at McDonald's in Bengkulu City. (X2) Product innovation has a significant effect on customer satisfaction at McDonald's in Bengkulu City, thus the higher product innovation, the higher customer satisfaction at McDonald's in Bengkulu City. (X3) Trust has a significant effect on customer satisfaction at McDonald's in Bengkulu City, thus the higher the trust, the higher the customer satisfaction at McDonald's in Bengkulu City. (X4) Food quality, product innovation and trust together show a significant influence on customer satisfaction. The test results show a significance value <0.05.